Prevalence and correlates of sleep quality in the Chinese college students with migraine: a cross-sectional study - Zhao, Jiayu; Cen, Yu; Yang, Jiaming; Liu, Chang; Li, Yajie; Ren, Zhen; Xiao, Yun; He, JinLong; Luo, Jing; Zhong, Yunling; Luo, Wenxiu; Wu, Jing; et al. (Frontiers in Behavioral Neuroscience, 2022)
Background: Migraineurs are often plagued by sleep disorders. The university student population is high in number and are likely to suffer from migraine. However, no study has analyzed the sleep quality of students with migraine and related contributing factors. Objective: We used the Pittsburgh Sleep Quality Index (PSQI) scale to assess the sleep of migraine patients among college students and to explore the influencing factors of sleep quality. Methods: We performed primary screening for migraine using the ID-migraine screening, and further assessed headache characteristics, sleep, anxiety, depression, and mobile phone addiction in college students with positive primary screening, then diagnosed migraine according to the third edition of the International Classification of Headache Disorders (ICHD-3). Finally, we analyzed the factors influencing sleep quality using Binary Logistic Regression Analysis. Those with scores greater than 5 points on the PSQI scale were believed to have poor sleep quality. Results: The prevalence of migraine was 6.6%. A total of 545 migraineurs were eventually included in the analysis, the incidence of poor sleep quality was 64.04%. The three factors of experiencing aura (OR=2.966, 95%CI=1.756-5.010, P<0.05), anxiety (OR=2.778, 95%CI=1.434-5.382, P<0.05), and high Mobile phone addiction index (MPAI) score (OR=1.025, 95%CI=1.002-1.049, P<0.05) contributed enormously to poor sleep quality. Moreover, the factors of aura symptoms (OR=3.796, 95%CI=2.041-7.058, P<0.05), anxiety (OR=3.146, 95%CI=1.473-6.719, P<0.05), and MPAI score (OR=1.028, 95%CI=1.002-1.054, P<0.05) influenced the sleep quality of female migraineurs rather than male migraineurs. Conclusions: The incidence of poor sleep quality is high among university students with migraine. Aura symptoms, anxiety, and high MPAI score influence the sleep quality of migraineurs, especially females. The proposal of prevention and intervention measures is of great importance to the physical and mental health of students with migraine.